2017
DOI: 10.1037/sah0000038
|View full text |Cite
|
Sign up to set email alerts
|

The effects of brief, passive psychoeducation on suicide literacy, stigma, and attitudes toward help-seeking among Latino immigrants living in the United States.

Abstract: Latino immigrants underutilize mental health treatment services compared with other ethnic groups, despite rates of mental illness that are comparable with those observed among the general population. With regard to suicidal behavior specifically, twice as many Latino suicide attempters do not seek or receive psychiatric services in the year prior to attempting suicide compared with non-Latino White attempters. The main objective of this study was to investigate whether provision of brief, passive psychoeducat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 91 publications
(171 reference statements)
1
30
0
Order By: Relevance
“…Sixteen studies were conducted in the U.S., United States [20][21][22][23] primarily in Washington DC (N = 5) [24][25][26][27][28], California (N = 3) [29][30][31], and New York (N = 3) [32][33][34]. Three were conducted in Europe (Denmark, Netherlands, and Norway) [35][36][37], and one each in Australia [38], Canada [39], and Taiwan [40].…”
Section: Study Characteristics and Interventionsmentioning
confidence: 99%
“…Sixteen studies were conducted in the U.S., United States [20][21][22][23] primarily in Washington DC (N = 5) [24][25][26][27][28], California (N = 3) [29][30][31], and New York (N = 3) [32][33][34]. Three were conducted in Europe (Denmark, Netherlands, and Norway) [35][36][37], and one each in Australia [38], Canada [39], and Taiwan [40].…”
Section: Study Characteristics and Interventionsmentioning
confidence: 99%
“…Low mental health literacy, stigma, and beliefs about treatment may be barriers to mental health care for Hispanics [41]. Dueweke and Bridges [42] examined whether passive psychoeducation (via brochures) would improve suicide literacy, stigma, and help-seeking attitudes among Hispanic immigrants. Results indicated that although suicide literacy improved, stigma toward suicidal individuals and attitudes toward seeking help did not.…”
Section: Suicide Prevention Interventions Among Hispanicsmentioning
confidence: 99%
“…All studies were conducted in North America; 15 in the USA and one in Canada. One study sought to increase care-seeking behaviour for Hepatitis B Virus (HBV) infection [28] and 15 studies for mental health problems (Table 1) [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…Health communication (the strategies used to inform, influence, and motivate audiences about health issues) [44] to increase care-seeking behaviour was tested in ten studies [28,30,[35][36][37][38][40][41][42][43], via three different approaches: entertainment education (EE), community outreach, and nonspecific approaches. Entertainment education (EE) refers to the placement of educational content within entertainment [45]; an approach employed by five studies.…”
Section: Health Communicationmentioning
confidence: 99%